Intrinsic and extrinsic fracto-mechanoluminescence of solids - Chandra, B P (Recent Research in Science and Technology, 2012)
Whereas nearly 50% of all inorganic salts and organic molecular solids exhibit the phenomenon of fracto ML., only a limited number of solids exhibit elastico ML and plastico ML. The fracto ML of certain crystals such as europium tetrakis (dibenzoyl methide) triethyl ammonium, ditriphenylphosphine oxide manganese bromide, Eu doped strontium aluminate ,impure saccharin, etc. is so intense that it can be seen in day light with naked eye. A large number of piezoelectric and non-piezoelectric organic and inorganic crystals exhibit intrinsic and extrinsic fracto-mechanoluminescence (ML) due to the electron bombardment and electron trapping mechanisms, and only a few crystals show ML due to the chemically-induced fracto-ML and other possible mechanisms. The charged surfaces produced during fracture of solids owing to piezoelectrification, defective-phase piezoelectrification, movement of charged dislocations, baro-diffusion of defects near the crack-tip, and many other processes may cause production of very high electric field near the charged surfaces. In the case of non-photoluminescent and non-cathodoluminescent materials, the high energy electrons may be emitted from the charged surfaces and the electron bombardment (EB) mechanism may excite the molecules of surrounding gases and subsequently the gas discharge ML may be produced. In photoluminescent and cathodoluminescent solids, the electron- bombardment may cause cathodoluminescence. In certain photoluminescent crystals, the light of gas discharge may excite photoluminescence. In many solids, the free electrons produced at fracture may be captured in the traps and consequently the electron-trapping (ET) mechanism may give rise to the light emission. Few solids may exhibit chemiluminescence because of the chemical reactions at the newly created surfaces. Some solids may exhibit black body radiations because of the high temperature produced near the tip of the moving cracks. Infrared radiation may also be emitted during the fracture of certain crystals. In certain solids, the gas discharge fracto ML and the photoluminescence excited by the gas discharge disappear when the solids are fractured inside liquids; however, in certain solids the solid state fracto ML appears even inside the liquids if they are not based on the processes involving gas discharge. Overall, depending on the prevailing conditions the ML spectra consist of either the gas discharge spectra or solid state luminescence spectra or the combination of the both. The understanding of the mechanism of fracto-ML may be useful in preparing suitable fracto- mechanoluminescent materials and it may be helpful in designing the fracto-ML based devices such as fracture sensor, impact sensor, damage sensors, safety management monitoring system, fuse system for army warheads, etc.